The Policy of Moving Civil Servants to Ibu Kota Nusantara: Perspective from Junior Civil Servants (Open Society Conference, 2023)
This paper explores the perspective of policy subject as an important factor in policymaking. Using the case of the moving civil servants to Ibu Kota Nusantara, this paper focuses on the perspective of junior civil servants as the first and foremost target for policy acceptance. In studying the policy analysis model, this paper attempts to assess the agonistic analysis model as an alternative to technocratic and proceduralism in policy. This rationality-based analysis model tends to bring up problematic positions between policymakers and policy subjects, with some cases where policy recipients lack advocacy. The data and information in this paper come from the results of in-depth interviews with representatives of young civil servants, studies of research reports, and studies of documents and reporting chronologically. This method was chosen to support the agonistic style of the constructivist analysis model.. The agonistic analysis model in the case of the ASN moving policy to IKN has general findings and reflections, namely: 1. It is necessary to see the construction and contextuality of the pros and cons in the policy, 2. It is necessary to map the dynamics or problems that will or have occurred in the policy, 3. It is necessary to accommodate vulnerable parties in the policy.